Analysis of survey data on corrosion in the automotive industry. (2021) - Chami, A.; Benabbou, R.; Taleb, M.; Rais, Z.; El haji, M.
Abstract: Automotive history and corrosion on a car go hand in hand. Research in all aspects of this field including protection, prevention measures and attempts to control corrosion could not solve the problem. Eventually, all the steel parts of the car start to corrode. Corrosion may not have an immediate effect on a material, but it does affect the strength, physical appearance, and can cause operating problems. Although automakers have made great strides in protecting bodywork and paintwork from this phenomenon through surface treatment and material selection, cars remain exposed to corrosion. In order to understand the phenomenon of corrosion, it is important to identify the types of corrosion, the mechanism and the prevention methods. The objective of this study is the statistical analysis of the phenomenon of corrosion in the automotive industry in Morocco. The statistical methods used in this work for analysis are Principal Components Analysis and Variable Association Methods. The data come from a survey using a total number of 100 questionnaires, which was completed by specialists in this field (Manufacturer services, laboratories, freelancers, expert in the automotive industry experts and researchers). These same specialists belong to 52% of all 121 companies, which are affiliated to the Moroccan Association for the Industry of Automotive Construction (MAIAC). The investigation expended over a period of 6 months. Survey enabled us to identify the areas of the vehicle affected by corrosion, the most frequent types of corrosion, the causes of this phenomenon and the parameters influencing corrosion of the materials composing a vehicle.